2021
DOI: 10.21608/bfemu.2021.139470
|View full text |Cite
|
Sign up to set email alerts
|

MRI Brain Tumor Segmentation Using Deep Learning. (Dept. E)

Abstract:  I. INTRODUCTIONRAIN tumor is an epidemic causes of cancer death. In USA, 700.000 people are diagnosed with brain tumors (80% benign and 20% malignant) [1]. In 2020, the American Cancer Society (ACS) for brain tumor estimated about 23,890 malignant tumors of the brain and around 18,020 deaths from malignant brain tumors [2]. Accurate segmentation and quantitative analysis of brain tumor is critical for tumor diagnosis and treatment planning.Magnetic resonance imaging (MRI) is usually used for brain tumor segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We applied the two models (Densenet and FCN-Alexnet) in the proposed system, since their decoders produce outputs that are of the same dimensions as the input image, which suits the task of segmentation. In addition, they have shown outstanding performance for several related medical applications, such as lung segmentation [17], [18], pulmonary cancerous detection [19], face recognition [20], brain cancer [21] and diabetic retinopathy [22].…”
Section: Methodsmentioning
confidence: 99%
“…We applied the two models (Densenet and FCN-Alexnet) in the proposed system, since their decoders produce outputs that are of the same dimensions as the input image, which suits the task of segmentation. In addition, they have shown outstanding performance for several related medical applications, such as lung segmentation [17], [18], pulmonary cancerous detection [19], face recognition [20], brain cancer [21] and diabetic retinopathy [22].…”
Section: Methodsmentioning
confidence: 99%
“…The ambiguity can be decreased, and the accuracy can be significantly increased by combining the tumor data that has been taken from many advanced networks. To gain more precise anatomical data on brain tumors, Nassar et al [ 20 , 21 ] fed the CNN model by integrating the image features of long skip-linked lesions. W. Chen et al [ 22 ] showed a separate 3D U-Net model that got around the memory limit by using different 3D convolutions.…”
Section: Related Workmentioning
confidence: 99%
“…2, the accuracy of the proposed multi-input Unet model for segmentation of whole tumor and core lesion is 0.92 and 0.90, respectively. Here, the algorithm proposed in references [48,49,52] inputs more lesion information into the deep learning network through pre-processing operation, which can improve the ability to obtain non-linear lesion features.…”
Section: Analysis Of the Proposed Multi-input Imagesmentioning
confidence: 99%
“…Thus, it can effectively improve the computational efficiency, but the model training still needs a large number of datasets. To solve this problem, Nassar et al [52] input the narrow-band information in the integrated MRI images into the CNN model, which can obtain more accurate brain tumor anatomical information. Kayalıbay et al [53] propose an improved CNN model based on the filter algorithm, which effectively alleviates the problem of high-class imbalance by combining the feature maps of long skip connected lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation